Eksistensi Ilmu Pengetahuan Islam di Era Disrupsi 4.0: Studi Takhrij dan Syarah Hadits - Bunga Sarah Istiqomah; Wahyudin Darmalaksana; Siti Chodijah (Gunung Djati Conference Series, 2022)
This study aims to discuss takhrij and syarah hadith related to the existence of science in the era of disruption 4.0. This study uses a qualitative approach that emphasizes literature review through the takhrij and syarah hadith methods with contemporary analysis. The results of this study indicate that the hadith narrated by Imam Tirmidhi No. 2570 relates to the existence of science in the current era of disruption 4.0. The status of the hadith is of hasan li ghairihi quality according to the criteria for the authenticity of the sanad and the matan of the hadith based on the takhrij hadith. While the hadith syarah shows that the existence of various Islamic sciences in the era of disruption 4.0 requires a review of the epistemological and axiological aspects so that they are more operational in responding to various contemporary challenges today. This study concludes that the hadith narrated by Imam Tirmidhi No. 2570 concerning the existence of science can be accepted (maqbul) so that it can be used as evidence. This study recommends to experts to strengthen the existence of Islamic science in the era of disruption 4.0.